Pengaruh Dana Pihak Ketiga Dan Non Performing Loan Terhadap Profitabilitas Perbankan Dengan Rasio Intermediasi Makroprudensial Sebagai Variabel Intervening - Hermanto Hermanto; Anita Anita (Universitas Katolik Soegijapranata, Semarang, 2022)
The purpose of this study is to investigate the impact of third party funds and non-performing loans on banking profitability by correlating Return on Assets with the macroprudential intermediation ratio as the mediating variable. This study uses information got from the yearly reports of banks recorded on the IDX with a sampling technique utilizing purposive sampling. The research period was taken for 5 years with the number of sample data used as many as 120 data from 24 banking sub-sector entities. The research method uses Partial Least Square (PLS) with secondary data types. The results of the research show that there is a positive impact of third party funds on the macroprudential intermediation ratio and there is no impact of non-performing loans on the macroprudential intermediation ratio, there is a partial negative impact of third party funds and non-performing loans on profitability, and there is a positive influence on the macroprudential intermediation ratio on profitability. Macroprudential intermediation ratio can mediate third party funds to profitability. However, the macroprudential intermediation ratio cannot mediate non-performing loans on profitability.